Knowledge integration framework: a systematic review - Said, Mahmoud E.; A. Jabar, Marzanah (School of Computing, College of Arts and Sciences, Universiti Utara Malaysia, 2018)
Knowledge integration within the organization translates the raw knowledge into actionable knowledge to solve organization problems. Knowledge used in this process can have different formalism that fall in two categories, logical based approach like first order logic, descriptive logic and, the other is non-logical based approach like natural language, ontology, semantic network etc. Many knowledge integration frameworks have been proposed to ease this complex process to ensure the result knowledge meet some quality attributes i.e. soundness, completeness etc. The aim of this study is to explore and analyse existing research in knowledge integration framework focusing on the formalism of raw knowledge and actionable knowledge as well as techniques used by knowledge integration framework and the limitations of those knowledge integration frameworks. This paper presents a systematic review of several researches which propose knowledge integration framework in last five years. We found most of researches use single formalism for raw and result knowledge. Little research insure actionable knowledge quality. Integration technique mainly depends on the formalism of raw and actionable knowledge.